Quality of life in Turkish haemodialysis patients - (:unkn) unknown (SPRINGER, 2005)
The aim of the study was to assess quality of life (QOL) in Turkish haemodialysis patients and to identify related socio-demographic and clinical variables. To measure QOL 100 patients completed SF-36 during regularly scheduled haemodialysis. We found that patients' QOL was substantially impaired. Age was negatively related to physical components of QOL. Duration of haemodialysis was negatively correlated with most of QOL dimensions. EPO treatment, education on disease and haemodialysis, and compliance to prescribed diet had great positive effects on QOL. Among the factors we have found to be related with the QOL in this study, probably the most important were education on disease and haemodialysis, and compliance to prescribed diet, in which we have influence, as nurses, on improving the QOL in patients receiving haemodialysis. The priority of renal nursing services should therefore be addressed to provide support in these areas.
Keywords: haemodialysis; quality of life